A substrate surface alloy strategy for integrated sulfide electrodes for sodium ion batteries with superior lifespan. Issue 15 (12th July 2021) - Zhou, Li-Feng; Du, Tao; Liu, Li-Ying; Wang, Yi-Song; Luo, Wen-Bin
Abstract : A binder-free free-standing sulfide electrode was synthesized and fabricated with a three-dimensional (3D) porous nanostructure. The surface of the Ni foam substrate was modified by the alloy strategy of pre-planting copper seeds on the Ni foam surface. Abstract : A binder-free free-standing sulfide electrode was synthesized and fabricated with a three dimensional (3D) porous nanostructure. In order to strengthen the adhesion between the substrate and active materials, the surface of the employed nickel foam substrate was modified by an alloy strategy of pre-planting copper seeds onto the nickel foam surface. The obtained electrode presents excellent electrochemical performance in sodium-ion batteries. It delivers a high reversible specific capacity of 1107 mA h g −1 at 0.1 A g −1 with an initial coulombic efficiency of 85.6%. Excellent rate and cycle performances were also exhibited. Even at 2 A g −1, it still can deliver a capacity of 475 mA h g −1 . The capacity retention is 61.8% after 1000 cycles at 0.5 A g −1 .